MiR-222-3p in Platelets Serves as a Distinguishing Marker for Early Recognition of Kawasaki Disease - Wang, Bo; Wang, Li-nong; Cheng, Fang-fang; Lv, Hai-tao; Sun, Ling; Wei, Dong-kai; Pu, Yu; Wu, Jie; Hou, Yuan-yuan; Wen, Bin; Xu, Xia-ping; Yan, Wen-hua (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is an acute vasculitis that 20% of which may develop coronary artery aneurysm in children if not appropriately treated. Therefore the early diagnosis of KD is essential for alleviating risk of acquiring heart disease. MicroRNAs (miRNAs) are a large class of small noncoding RNAs which post-transcriptionally regulate gene expression and have been shown to play critical roles in numerous biological processes and diseases. In this study, we use high-throughput miRNA sequencing and find dozens of miRNAs are highly expressed in platelets. By comparing the miRNA expression profile of platelets of acute KD patients and other febrile patients, miR-222-3p is validated to be significantly upregulated in platelets of acute KD patients. Further KEGG pathway analysis shows that targets of miR-222-3p are enriched in immune-related signaling pathways. Our study uncovers the potential of miR-222-3p in platelets as biomarker for early diagnosis of Kawasaki disease.